2022
DOI: 10.1108/qae-02-2022-0037
|View full text |Cite
|
Sign up to set email alerts
|

The role of leadership in effective implementation of quality assurance mechanisms in higher education: an exploratory case study from Pakistan

Abstract: Purpose This study aims to explore whether and how leaders’ attributes, understanding of and attitude towards quality assurance (QA) shape their practices towards effective implementation of QA in universities. Design/methodology/approach Using qualitative case study, the data were collected from nine institutional leaders purposively selected from two universities. The data, collected through semi-structured interviews, were analysed using thematic analysis technique. Findings The findings revealed that p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 44 publications
(68 reference statements)
0
2
0
Order By: Relevance
“…This is one of the primary quantitative studies on the intellectual competencies of QEC leaders on major functions of the QEC department as well as on institutional performance. Findings indicated that intellectual competencies are fruitful for the optimization of major functions allocated to QEC and hence find consistent with Ahmad and Ahmed (2022). Therefore, it is optimal to appreciate the use of Malcolm Bridge theory, as used by Noor et al (2022), and order to discuss the intellectual competencies of leaders as indicated by Meredith and Mantel (2012) and Meredith et al (2017).…”
Section: Conclusion and Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“…This is one of the primary quantitative studies on the intellectual competencies of QEC leaders on major functions of the QEC department as well as on institutional performance. Findings indicated that intellectual competencies are fruitful for the optimization of major functions allocated to QEC and hence find consistent with Ahmad and Ahmed (2022). Therefore, it is optimal to appreciate the use of Malcolm Bridge theory, as used by Noor et al (2022), and order to discuss the intellectual competencies of leaders as indicated by Meredith and Mantel (2012) and Meredith et al (2017).…”
Section: Conclusion and Discussionmentioning
confidence: 72%
“…Similarly, rear studies are done to relate intellectual competencies of QEC leader with quality management in HEIs. Few of the conducted studies include Ahmad and Ahmed (2022) and Ali et al (2018). However, none of these studies explore the concept through inferential statistics as Ali et al (2018) is a form of descriptive research and predicts the impact of intellectual competencies on the bases of correlation.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…Leaders, in this case, rectors, vice-rectors, deans, vice-deans and their clear vision of excellence, are those who use their power to influence and motivate academic teachers and researchers for the betterment of themselves as well as for the organization (Anyamele, 2007;Nasriman et al, 2016;Jensen et al, 2017;Hasnawi et al, 2021). The role of leadership is significant to the success of any university (Osseo-Asare et al, 2005;Sharabi, 2013;Ahmad and Ahmed, 2022). Leadership representatives and their pioneer mentality (Abatayo and Regis, 2018) have a very crucial influence on employees' attitudes toward their job and everyday commitment (Saleem, 2015;Torlak and Kuzey, 2019;Jamalia et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…The role of leadership is significant to the success of any university (Osseo‐ Asare et al. , 2005; Sharabi, 2013; Ahmad and Ahmed, 2022). Leadership representatives and their pioneer mentality (Abatayo and Regis, 2018) have a very crucial influence on employees' attitudes toward their job and everyday commitment (Saleem, 2015; Torlak and Kuzey, 2019; Jamalia et al.…”
Section: Discussionmentioning
confidence: 99%